ASSESSMENT OF SAFETY INDEX AND FUNCTIONAL POTENTIAL OF THE SHELLFISH Cardiosoma armatum IN RELATION TO SEX DIFFERENCES - Moruf, R. O.; Ajimo, M. A.; Muhd, I. U.; Oluboba, T. F.; Lawal-Are, A.O. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
This study analyzed the mineral safety index (MSI) and functional potential of Cardiosoma armatum with a focus on sex differences. Significant variations were observed between male and female crabs, with the shell consistently acting as a major mineral reservoir. In females, calcium (988.95 mg/100g) and magnesium (26.33 mg/100g) concentrations were significantly higher in the shell compared to the flesh, showing 92.67% and 87.08% differences, respectively. Similar trends were observed in males, where calcium (1210.32 mg/100g) and magnesium (19.22 mg/100g) exhibited 92.62% and 82.92% disparities between shell and flesh. The MSI indicated that the shell provides a critical mineral reserve, with calcium, magnesium, and phosphorus exhibiting notable deviations from the Recommended Allowance Intake (RAI). Functional properties also varied by sex, with males showing higher packed bulk density (0.52 g/ml), oil absorption (102.64%), and dispersibility (62.80%), whereas females exhibited higher solubility (21.24%). These findings highlight the sex-dependent differences in both mineral distribution and functional characteristics, which may inform their use in food processing and nutrition.